2020
DOI: 10.5187/jast.2020.62.5.692
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of crust derived from dry-aged Holstein and Hanwoo loin

Abstract: This study evaluated the quality characteristics of crust derived from dry-aged Holstein and Hanwoo loins and their effects on food as additives. With respect to physicochemical properties, we examined the proximate composition, pH value, salinity, color, water and fat absorption, emulsifying capacity, and swelling yield. The protein and ash contents in the Holstein crust were significantly higher than those in the Hanwoo crust (p < 0.0001). The fat content in the Hanwoo crust was significantly higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These findings are consistent with those of a study in which the protein, fat, and ash contents of beef patties increased proportionally when okara, a protein additive, was added to them ( Turhan et al, 2009 ). The changes in the proximate composition of sausage may be due to the proximate composition of the freeze-dried Hanwoo crust (water: 1.2%; protein: 44.06%; fat: 49.33%; ash: 1.95%) added in the process of sausage production, resulting in different proximate compositions for the Hanwoo crust treatments ( Lee and Kim, 2020 ). As noted above, crust is known to have high protein and ash contents due to surface moisture loss through evaporation during dry aging ( Campbell et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of a study in which the protein, fat, and ash contents of beef patties increased proportionally when okara, a protein additive, was added to them ( Turhan et al, 2009 ). The changes in the proximate composition of sausage may be due to the proximate composition of the freeze-dried Hanwoo crust (water: 1.2%; protein: 44.06%; fat: 49.33%; ash: 1.95%) added in the process of sausage production, resulting in different proximate compositions for the Hanwoo crust treatments ( Lee and Kim, 2020 ). As noted above, crust is known to have high protein and ash contents due to surface moisture loss through evaporation during dry aging ( Campbell et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it has been reported that the added soy protein isolate as a protein additive suppresses water and fat loss of the emulsion, thus increasing the emulsion stability and the viscosity ( Joseph, 1987 ; Raokosky, 1970 ). Lee and Kim (2020) compared the emulsifying power of the crusts derived from dry-aged sirloin samples of Hanwoo and Holstein, and found that Hanwoo considerably outperformed Holstein , proving that it is an efficient emulsion binder. In this study as well, the emulsifying power of sausage emulsion was enhanced by the addition of Hanwoo crust with excellent emulsifying properties, which in turn enhanced its viscosity.…”
Section: Resultsmentioning
confidence: 99%
“… n.a., not available. The information was adapted from Zdanowska-Sasiadek et al ( 2 ), Mishra et al ( 21 ), Mgbemere et al ( 79 ), Chukwu and Imodiboh ( 80 ) and Lee and Kim ( 2 , 21 , 79 81 ). …”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…However, the crust formed during the dry-aging process is the reason for the high price of dry-aged meat compared to other meat types. The crust is the area of meat formed by surface hardening during the dry-aging process, and its use as edible meat is limited ( Dashdorj et al, 2016 ; Lee and Kim, 2020 ). Nevertheless, the crust is enriched with flavor components due to surface moisture evaporation ( Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%